How the stock market reacts on presidential inauguration and cabinet announcement? A case study of Indonesian mining and energy industries - Achmad Rizal; Imas Hasanah; U'um Munawaroh; Dwi Martutiningrum (Nur Science Institute, 2025)
This study investigates the stock market reaction of Indonesia’s mining and energy sectors, represented by LQ45 index constituents, toward the 2024 presidential inauguration and cabinet announcement. Using an event study methodology with an event window of t-7 to t+7, the research measures market responses through abnormal returns based on the market-adjusted model. Results show that the pre-inauguration period is characterized by predominantly negative Average Abnormal Returns (AAR) and Cumulative Abnormal Returns (CAR), indicating heightened uncertainty surrounding the incoming administration. On the inauguration day, both indicators turn positive, reflecting temporary optimism regarding political stability and policy continuity. However, the post-event window displays volatility, with sharp positive abnormal returns on certain days (e.g., t+3) but declines on others (e.g., t+2). Most t-statistics are statistically insignificant, suggesting that the inauguration did not generate strong or persistent market reactions.